A summary of the statistical aspects of the procedures for resolving potential employment discrimination recently issued by the Office of Federal Contract Compliance along with a commentary. (7th March 2022) - Gastwirth, Joseph L
Abstract: On 5 November 2020, the Office of Federal Contract Compliance in the Department of Labor issued new rules codifying the procedures it will use to resolve equal employment issues. First, this article summarizes the new rules focusing on how the agency will use and evaluate statistical evidence in its monitoring of government contractors' compliance with equal employment laws. After noting the diminished role of statistical evidence in the new rules, the likely effect of them on the use of statistical data and analyses in equal employment proceedings are explored. The logical and statistical reasoning underlying several aspects of the new rules is also questioned. Because the new rules refer to a report of the Chamber of Commerce that, in part, criticized the agency from bringing a case against a firm, data from the case are re-analyzed. The statistical analysis provides support for the position of OFCCP.